Parvovirus B19 NS1 protein induces synovitis mimicking rheumatoid arthritis - Yen, Chang-Yi; Tseng, Chia-Chun; Lin, Chia‐Hui; Lin, Yuan‐Zhao; Li, Ruei‐Nian; Wang, Pin-Yi; Chen, Kuan-Yu; Wu, Cheng-Chin; Ou, Tsan-Teng; Chen, Chung-Jen; Liu, Yu-Peng; Yen, Jeng-Hsien (Scientific reports, 2025)
This study aims to investigate the role of parvovirus B19 infection in the pathogenesis of rheumatoid arthritis (RA). B19-NS1 DNA was cloned into the LentiORF pLEX-MCS vector, then co-transfected with the pLEX-MCS-NS1 vector and packaging system to produce LEX-NS1 lentiviral stock. LEX was also prepared as the control. Transduction of LEX-NS1 or LEX lentivirus into the SW982 cell line then proceeded, and total RNA was extracted for RNA-seq. Pathway analysis and comparison of pathway status between this study and GEO datasets were performed, demonstrating that acute phase response signaling, NRF2-mediated oxidative stress response, and mTOR signaling pathways were activated after the transduction of LEX-NS1 into the SW982 cell line, although the interferon signaling pathway was inhibited. The comparison of all pathways using hierarchical clustering showed that the pathway status after transduction of B19-NS1 was closer to RA than that in osteoarthritis. Similar findings can also be found in cellular immune, humoral immune, cytokine, apoptosis, cellular growth, cellular stress, growth factor, and intracellular pathways. In conclusion, parvovirus B19-NS1 can induce inflammation of the synovium mimicking synovitis in RA; therefore, parvovirus B19 infection might be one of the trigger factors in the pathogenesis of RA.